Afrikaanse Spreekwoorde en Uitdrukkings: ’n makrostrukturele beskouing - Beuke-Muir, Chrisna (Lexikos, 1999)
Afrikaanse Spreekwoorde en Uitdrukkings: A Macrostructural Study. A restricted synchronic dictionary such as Afrikaanse Spreekwoorde en Uitdrukkings has an important role to play in modern lexicography where user-friendly reference sources facilitate communication. A considerable number of theoretical guidelines exist for the choice of lexicon items to be included in a dictionary, and this review article attempts to provide some pointers. The research also includes sociolinguistic implications which result from the compilation of the macrostructure of a particular dictionary. The focal points are firstly taboos to which lexicographers of Afrikaans dictionaries are subjected, and secondly establishing which expressions fall within the limits of idiomatic language usage. The treatment of idiom-like collocations particularly appears to be problematic. Another issue which will be considered briefly, is the morphological presentation of lemmas.